2018
DOI: 10.1016/j.aju.2018.05.006
|View full text |Cite
|
Sign up to set email alerts
|

The first Iraqi experience in sacral neuromodulation for patients with lower urinary tract dysfunction

Abstract: ObjectivesTo present our experience, in Iraq, with sacral neuromodulation (SNM) in patients with refractory lower urinary tract dysfunction, with discussion of the factors that affect the response rate.Patients and methodsIn this prospective, clinical, interventional study, 24 patients were evaluated and treated by a team comprised of a Urologist and a Neurosurgeon with SNM over a 1.5-year period. The gender, age, pathology, and clinical presentation, were all studied and evaluated. Successful clinical respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
0
7
1
Order By: Relevance
“…The percentage of those patients who continued to have a positive response at 6 months after intervention was good and comparable in both arms of the study, as has been found in other studies of BTX and SNM [ 10 , 15 , 16 ]. It was even higher than the percentage of durable response achieved in our earlier study on SNM [ 7 ], which is due to the fact that in the earlier study, patients with neurogenic OAB were also included, while in the present study only patients with idiopathic OAB were included.…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…The percentage of those patients who continued to have a positive response at 6 months after intervention was good and comparable in both arms of the study, as has been found in other studies of BTX and SNM [ 10 , 15 , 16 ]. It was even higher than the percentage of durable response achieved in our earlier study on SNM [ 7 ], which is due to the fact that in the earlier study, patients with neurogenic OAB were also included, while in the present study only patients with idiopathic OAB were included.…”
Section: Discussioncontrasting
confidence: 57%
“…Three patients in the SNM group had a diminution in response during the follow-up months, which was either due to IPG dysfunction or explained by the theory that possibly different brain areas were affected during different periods of neuromodulation (early and late), which may account for the change in response in some patients with time [ 7 ]. Weil et al [ 14 ] also reported an important association between late loss of therapeutic response and the existence of former psychiatric problems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty-one studies comprising a total of 887 patients were included in the meta-analysis of test SNM and the pooled test SNM success rate was 66.2% (95% CI 56.9–74.4) (Fig. 4 a) [ 21 , 29 , 32 50 ]. Twenty-four studies with a total of 428 patients were included in the meta-analysis of permanent SNM [ 21 , 26 , 29 , 31 38 , 40 , 42 – 45 , 48 , 49 , 51 56 ].…”
Section: Resultsmentioning
confidence: 99%